Nowe oblicze bezrobocia - Ślebarska, Katarzyna (Śląskie Studia Historyczno-Teologiczne, 2010)
The article undertakes the critical topic, namely the problem of unemployment, that is still a great sociological and psychological problem in Poland. The analysis of the changes, that has occurred since 1990 depicts the unemployment as the dynamic process rather than static issue. Accordingly, described problems influenced by personal as well as environmental factors. This report consider also the culture that has a significant impact on the perception and behaviours undertaken by the unemployed.